Green manuring and nutrient management impacting soil properties and sustainability of mango orchard - KUMAR, KAILASH; ADAK, TARUN; SINGH, VINOD KUMAR (Journal of Soil and Water Conservation, 2020)
In view of declining soil health and mango orchard productivity, an experiment was laid out to evaluate the effect of organic and inorganic fertilizers on nutrient dynamics and mango orchard productivity in Lucknow region. Soil organic carbon content varied between 0.41 to 0.61 % (0-30 cm) and less than 0.34% (30-60 cm) across different treatments. The highest average available P and improvement in K availability was noticed wherever green manuring (GM) or farm yard manure (FYM) along with NPK was added. Similarly, a positive effect of integrated nutrient management on enhanced availability of DTPA extractable micronutrients (Zn, Cu, Fe and Mn) was inferred. A wide range of yield variation was recorded across the seasons and treatments. Addition of FYM improved sustainability index (0.58) while green manuring further improved it (0.66) as compared to control (0.43). TSS and ascorbic acid content ranged between 17.8 to 20.3 0B and 19 to 36.3 mg/ 100g, respectively. Ascorbic acid content was significantly differing among the treatments while TSS and acidity was not much affected. The present study concluded that inclusion of green manuring/FYM as a component in integrated nutrient management system in low fertile mango orchard soils had positive effect on soil quality and sustainable fruit productivity.